Linking agriculture to nutrition: the evolution of policy. Issue 4 (24th June 2020) - Fan, Shenggen; Yosef, Sivan; Pandya-Lorch, Rajul
Abstract : Purpose: The purpose of this paper is to summarize the evolution of global and national policies linking agriculture to nutrition in 2010–2020, and provides insights on the recent policy trajectory in China to illustrate how individual countries are addressing agriculture and nutrition. Design/methodology/approach: The authors utilize a noncomprehensive review of gray and peer-review literature, as well as a case study approach. Findings: Select countries have made initial strides in linking agriculture and nutrition through policy, though progress is not widespread and uneven. Practical implications: Researchers can begin closing the existing knowledge gaps on agriculture and nutrition. Policymakers can learn from the country lessons and experiences in agriculture and nutrition policy. Originality/value: This paper provides one of the only overviews of global policy on agriculture and nutrition during the period 2010–2020.